2022
DOI: 10.3389/fendo.2022.972312
|View full text |Cite
|
Sign up to set email alerts
|

The role of protein acetylation in carcinogenesis and targeted drug discovery

Abstract: Protein acetylation is a reversible post-translational modification, and is involved in many biological processes in cells, such as transcriptional regulation, DNA damage repair, and energy metabolism, which is an important molecular event and is associated with a wide range of diseases such as cancers. Protein acetylation is dynamically regulated by histone acetyltransferases (HATs) and histone deacetylases (HDACs) in homeostasis. The abnormal acetylation level might lead to the occurrence and deterioration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 300 publications
0
15
0
Order By: Relevance
“…Tubulin is the target of many anticancer drugs. 421 Tumors are resistant to apoptosis. PDCD5, a protein related to apoptosis, can bind to Tip60 and increase p53 acetylation at K120, which affects the expression of apoptosis‐related genes such as Bax .…”
Section: Acetylationmentioning
confidence: 99%
See 2 more Smart Citations
“…Tubulin is the target of many anticancer drugs. 421 Tumors are resistant to apoptosis. PDCD5, a protein related to apoptosis, can bind to Tip60 and increase p53 acetylation at K120, which affects the expression of apoptosis‐related genes such as Bax .…”
Section: Acetylationmentioning
confidence: 99%
“…Increasing evidence shows that carcinogenesis is affected by metabolism in the body. Most metabolic proteins are substrates of lysine acetylation, 421 such as ATM, ABL1, CDK9, BTK, and CDK1. PKM2 is the last rate‐limiting enzyme in the glycolytic pathway responsible for the conversion of phosphoenolpyruvate to pyruvate.…”
Section: Acetylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Two families of antagonistic enzymes control histone acetylation: Histone acetyltransferases (HATs), which acetylate lysine residues at the N-terminus of histone proteins, and HDACs, which remove acetyl groups from histones. Histone acetylation reduces attraction between negative and positive charges of DNA and histone tails, respectively ( 90 , 91 ). This structural change favors the decompaction of chromatin, allowing access to the gene sequence for its transcription.…”
Section: Epigenetic Mechanisms In Cancer Roles In Carcinogenesis and ...mentioning
confidence: 99%
“…Additionally, Seetharaman and colleagues have shown that the protein Talin recruits αTAT1 to the focal adhesions where the MT acetylation is critical for fine-tuning the mechanosensitive cell adhesion and migration [ 327 ]. This role of acetylated α-tubulin Lys40 in cell migration has been explored in oncology, with several studies targeting MT acetylation as a chemotherapeutic approach [ 328 ].…”
Section: Tubulin Acetylation: Structural and Functional Implicationsmentioning
confidence: 99%